Comparison of In Vitro Activity of Cephalexin, Cephradine, and Cefaclor - Bill, Nancy J. (1977)
Inhibitory activity of cephalexin, cephradine, and cefaclor was compared by the WHO-ICS agar dilution technique. Cefaclor was substantially more active against staphylococci, streptococci, gonococci, meningococci, Haemophilus, Escherichia coli, Klebsiella pneumoniae, Citrobacter diversus, Proteus mirabilis, salmonellae, and shigellae than was cephalexin, which in turn was more active than cephradine. Cefaclor appeared to be less resistant to staphylococcal penicillinase than did the other two agents. None of these cephalosporins was active against Enterobacter, Serratia, indole-positive Proteeae, Pseudomonas, or Bacteroides fragilis.